Contamination Level, Distribution, and Inventory of Dechlorane Plus (DP) in the Surface Soil of Shenyang City, China - Hui Wang; Siyi Yu; Tony R. Walker; Hao Wu; Xiaoxu Wang; Yueli Yang; Yinggang Wang (Toxics)
Dechlorane Plus (DP), an emerging type of persistent organic pollutant (POP), poses potential harmful effects on plants, animals, and humans alike, garnering increasing attention. Urban surface soil is easily accessible to urban residents, and its environmental conditions have a more significant impact on urban residents. However, there are few studies on related DP contamination. In this study, the contamination of DP in surface soil from Shenyang City, Liaoning Province, China, was investigated. Soil samples were collected from 33 different locations in May and June 2023. The total DP (∑DP), anti-DP, and syn-DP were determined by gas chromatography and ranged from not detected (ND) to 77.80 ng/g, from ND to 61.50 ng/g, and from ND to 16.30 ng/g, respectively. The mean values were 33.60 ± 18.93 ng/g, 27.01 ± 14.32 ng/g, and 8.57 ± 4.55 ng/g. The findings indicate that anti-DP is more readily detectable than syn-DP, attributable to the lower proportion of syn-DP in the overall DP production and the distinct physicochemical properties of DP isomers. The fsyn [syn-DP/(anti-DP + syn-DP)] is 0.14–0.40, with a mean value of 0.22. This aligns closely with the values observed in commercial DP formulations, suggesting that the primary sources are derived from commercial DP products. Contour maps show that DP concentrations are influenced by urban land use and DP production. Based on the Tyson polygon method, the DP inventory was calculated at approximately 1.18 tons, with the unit area load exceeding previously reported values. The results also show that the health risks of DP are minimal, but children are more susceptible to the impacts of DP than adults, and oral ingestion is a more critical exposure pathway.